A large‐solid‐angle X‐ray Raman scattering spectrometer at ID20 of the European Synchrotron Radiation Facility. (16th February 2017) - Huotari, S.; Sahle, Ch. J.; Henriquet, Ch.; Al-Zein, A.; Martel, K.; Simonelli, L.; Verbeni, R.; Gonzalez, H.; Lagier, M.-C.; Ponchut, C.; Moretti Sala, M.; Krisch, M.; et al.
Abstract : An end‐station for X‐ray Raman scattering spectroscopy at beamline ID20 of the European Synchrotron Radiation Facility is described, dedicated to the study of shallow core electronic excitations using non‐resonant inelastic X‐ray scattering. Abstract : An end‐station for X‐ray Raman scattering spectroscopy at beamline ID20 of the European Synchrotron Radiation Facility is described. This end‐station is dedicated to the study of shallow core electronic excitations using non‐resonant inelastic X‐ray scattering. The spectrometer has 72 spherically bent analyzer crystals arranged in six modular groups of 12 analyzer crystals each for a combined maximum flexibility and large solid angle of detection. Each of the six analyzer modules houses one pixelated area detector allowing for X‐ray Raman scattering based imaging and efficient separation of the desired signal from the sample and spurious scattering from the often used complicated sample environments. This new end‐station provides an unprecedented instrument for X‐ray Raman scattering, which is a spectroscopic tool of great interest for the study of low‐energy X‐ray absorption spectra in materials under in situ conditions, such as in operando batteries and fuel cells, in situ catalytic reactions, and extreme pressure and temperature conditions.